Mbnl1-mediated alternative splicing of circMlxipl regulates Rbbp6-involved ChREBP turnover to inhibit lipotoxicity-induced β-cell damage - Gong, Yingying; Wei, Meilin; Cao, Xiaopei; Xu, Changliu; Jin, Jiewen; Pei, Ling; Li, Yanbing; Xiao, Haipeng; Wu, Liting (Molecular medicine (Cambridge, Mass.), 2024)
Diabetes, a global epidemic, is the leading cause of mortality globally. The aim of this study is to get better understanding of pathophysiology of diabetes. Palmitic acid (PA)-treated β-cells, db/db mice and high fat diet (HFD)-fed mouse model of type 2 diabetes were established. H&E was used to assess the histological changes of pancreas. IHC, FISH, western blot or qRT-PCR was employed to detect the expression of key molecules in primary islets or lipotoxic β-cells. Cell behaviors were detected by MTT, EdU incorporation assay, TUNEL assay and glucose-induced insulin secretion (GSIS). The associations among circMlxipl, Mbnl1 and Rbbp6 were validated by RIP and RNA pull-down assays, and the direct binding between Hdac3 and Mbnl1 promoter was examined by ChIP and luciferase assays. Co-IP was employed to assess the interaction between ChREBP and Rbbp6, as well as the ubiquitination of ChREBP. Hdac3 and ChREBP were upregulated, but Mbnl1 and circMlxipl were downregulated in islets from diabetic mice and lipotoxic β-cells. Mbnl1 overexpression protected against PA-induced impairments in lipotoxic β-cells through modulating back-splicing of circMlxipl and suppressing ChREBP. Hdac3 served as a transcriptional repressor of Mbnl1, and it was implicated in circMlxipl-mediated protection via regulating ChREBP expression in lipotoxic β-cells. Lack of circMlxipl inhibited Rbbp6-mediated ubiquitin-proteasomal degradation of ChREBP in lipotoxic β-cells. In vivo studies revealed that Hdac3 knockdown or Mbnl1 overexpression alleviated diabetes symptoms through circMlxipl-regulated ChREBP in diabetic mice. Mbnl1-mediated alternative splicing of circMlxipl regulates Rbbp6-involved ChREBP turnover to inhibit lipotoxicity-induced β-cell damage.